1995
DOI: 10.1007/bf00374154
|View full text |Cite
|
Sign up to set email alerts
|

Rapid onset and calcium independence of the gap junction uncoupling induced by heptanol in cultured heart cells

Abstract: The kinetics of the reversible interruption of gap junction communication by the aliphatic alcohol heptanol and the possible mediation of an increase of the cytosolic Ca2+ concentration have been investigated in pairs of myocytes dissociated from neonatal rat ventricles and cultured for 2-3 days. Junctional communication was estimated by measuring either the cell-to-cell electrical conductance with a double whole-cell voltage-clamp method, or the rate constant of dye diffusion with the fluorescence recovery af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…1B), it seems unlikely that n-alkanols and arachidonic acid act via intracellular H + and/or Ca 2+ . This conclusion agrees with previous observations that n-heptanol and arachidonic acid do not elevate [Ca 2+ ] i in rat heart cells and lacrimal gland cells ( [4,11,15]; but see also [14]. It is also consistent with the time course of uncoupling and recoupling during rapid application and removal of n-heptanol (0.5 s [4]).…”
Section: Site Of Action Of Lipophilic Agentssupporting
confidence: 93%
See 1 more Smart Citation
“…1B), it seems unlikely that n-alkanols and arachidonic acid act via intracellular H + and/or Ca 2+ . This conclusion agrees with previous observations that n-heptanol and arachidonic acid do not elevate [Ca 2+ ] i in rat heart cells and lacrimal gland cells ( [4,11,15]; but see also [14]. It is also consistent with the time course of uncoupling and recoupling during rapid application and removal of n-heptanol (0.5 s [4]).…”
Section: Site Of Action Of Lipophilic Agentssupporting
confidence: 93%
“…Burt et al [10] proposed that lipophilic agents produce local disorder at the lipid-protein interface of cell membranes which leads to conformational changes of connexins and hence connexon dysfunction. Bastide et al [4] recently reported that [Ca 2+ ] i is not involved in n-heptanol-dependent uncoupling.…”
Section: Introductionmentioning
confidence: 99%
“…The two substance classes alcohols and saponins probably act on gap junctional conductance by two different mechanisms. Alcohols are thought to interrupt cell-cell communication by direct interaction with channel proteins or with their lipid environment (Bastide et al, 1995), while AGA most likely disrupts connexon particle arrangement within gap junction plaques (Goldberg et al, 1996; see also Kumar and Gilula, 1996).…”
Section: Do Uncoupling Agents Affect Astrocyte [Na 1 ] I By Blocking mentioning
confidence: 99%
“…Heptanol is one of several lipophilic agents known to inhibit gap junctions reversibly [4,15,17,22]. In both normal dog hearts [6] and the canine model of healed myocardial infarction [7] selective intracoronary infusion of heptanol increases the susceptibility to arrhythmias, consistent with altered cellular coupling being an important risk factor for arrhythmogenesis [37].…”
Section: Introductionmentioning
confidence: 99%